Influence of hydrocortisone infusion method on the clinical outcome of patients with septic shock: A systematic review and meta-analysis - Yuting Li; Youquan Wang; Jianxing Guo; Dong Zhang (Journal of Intensive Medicine)
Background: The effect of the modality of hydrocortisone administration on clinical outcomes in patients with septic shock remains uncertain. This systematic review and meta-analysis evaluate the impact of intermittent bolus and continuous infusion of hydrocortisone on these outcomes. Methods: We searched the PubMed, Embase databases, and Cochrane Library for randomized controlled trials (RCTs) and cohort studies published from inception to January 1, 2023. We included studies involving adult patients with septic shock. All authors reported our primary outcome of short-term mortality and clearly compared the clinically relevant secondary outcomes (ICU length of stay, hospital length of stay, vasopressor-free days, hyperglycemia, hypernatremia, and ICU-acquired weakness [ICUAW]) of intermittent bolus and continuous infusion of hydrocortisone. Results were expressed as odds ratio (OR) and mean difference (MD) with accompanying 95% confidence interval (CI). The PROSPERO registration number is CRD42023392160. Results: Seven studies, including 554 patients, were included. The primary outcome of this meta-analysis showed no statistically significant difference in the short-term mortality between intermittent bolus and continuous infusion groups (OR=1.21, 95% CI: 0.84 to 1.73; P=0.31; Chi2=9.06; I2=34%). Secondary outcomes showed no statistically significant difference in the ICU length of stay (MD=−0.15, 95% CI: −2.31 to 2.02; P=0.89; Chi2=0.95; I2=0%), hospital length of stay (MD=0.63, 95% CI: −4.24 to 5.50; P=0.80; Chi2=0.61; I2=0%), vasopressor-free days (MD=−1.18, 95% CI: −2.43 to 0.06; P=0.06; Chi2=2.48; I2=60%), hyperglycemia (OR=1.27, 95% CI: 0.80 to 2.02; P=0.31; Chi2=5.23; I2=43%), hypernatremia (OR=0.93, 95% CI: 0.44 to 1.96; P=0.85; Chi2=0.37; I2=0%), or ICUAW (OR=0.83, 95% CI: 0.36 to 1.94; P=0.67; Chi2=0.90; I2=0%) between the two groups. Conclusions: This meta-analysis indicated no significant difference in short-term mortality between intermittent bolus or continuous hydrocortisone infusion in patients with septic shock. Additionally, the hydrocortisone infusion method was not associated with ICU length of stay, hospital length of stay, vasopressor-free days, hyperglycemia, hypernatremia, or ICUAW.